2016
DOI: 10.1002/2015gl067373
|View full text |Cite
|
Sign up to set email alerts
|

Propagation properties of quasiperiodic VLF emissions observed by the DEMETER spacecraft

Abstract: Quasiperiodic (QP) emissions are electromagnetic waves in the frequency range of about 0.5–4 kHz observed in the inner magnetosphere that exhibit a periodic time modulation of the wave intensity, with modulation periods from a few seconds up to 10 min. We present results of a detailed wave analysis of nearly 200 events measured by the low‐altitude Detection of Electro‐Magnetic Emissions Transmitted from Earthquake Regions (DEMETER) spacecraft. Upper frequency range of studied emissions was limited to 1 kHz due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 42 publications
(51 reference statements)
4
43
0
Order By: Relevance
“…Ongoing research of QP waves with unique behavior on small latitudinal scales is important since they are naturally smoothed out in large statistics due to averaging [ Hayosh et al , ]. Figure presents spectrograms of power spectral density of electric field and θ kB angle for another two QP events showing the same characteristics as the event we have analyzed in Figure .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ongoing research of QP waves with unique behavior on small latitudinal scales is important since they are naturally smoothed out in large statistics due to averaging [ Hayosh et al , ]. Figure presents spectrograms of power spectral density of electric field and θ kB angle for another two QP events showing the same characteristics as the event we have analyzed in Figure .…”
Section: Discussionmentioning
confidence: 99%
“…However, as the burst mode was mostly triggered at lower latitudes, data from latitudes higher than 50° were available only in about 140 cases of QP events. According to the results of Hayosh et al [], the observed direction of the Poynting vector is mostly downward, nearly perpendicular to the ground, and the dependence of θ kB on λ mag is fairly linear, decreasing from θ kB ≈70° at λ mag =50 ∘ to θ kB ≈30 ∘ at λ mag =60 ∘ .…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, sometimes the event is observed by DEMETER at locations very close to Kannuslehto, but it is absent in the Kannuslehto data. This indicates that the waves may have difficulties penetrating from the DEMETER altitudes down to the ground, which seems to be consistent with their unducted propagation [ Němec et al , ; Titova et al , ; Hayosh et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…The main discrepancy between the modeling and observation results is for the upper frequency which is about 3 and 1.9 kHz, respectively (the frequency range in Figure a is limited to 2 kHz for consistency with Figure a in Hayosh et al, ). This could be related to the peculiarities of the wave propagation from the source to the point of their detection (Hayosh et al, ; Němec et al, ; Němec, Bezděková, et al, ; Němec, Hospodarsky, et al, ). In particular, the wave ducting becomes less efficient, and therefore, effective losses could increase as the frequency approaches one half of the electron gyrofrequency at the equator (which is equal to ≈6.9 kHz for L =4.0).…”
Section: Results Of Numerical Simulationsmentioning
confidence: 99%